2008
DOI: 10.1007/s10439-008-9439-6
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Patterns Affect Cell Distributions on Injection-Molded Poly-l-Lactide Substrate

Abstract: The effects of residual intra-substrate stress distribution on cell behavior have not been systematically investigated. Thus, the objective of this research was to analyze the relationship between cell distribution and internal stress patterns. A photoelastic method was used for residual stresses identification. Poly-L-lactide (PLLA) discs were prepared using an injection molding technique. MG-63 and NIH-3T3 cells were cultured on the surface of the PLLA disc. The cell distributions for high and low-stress reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Poly-L-lactide (PLLA) has become the most popular bioresorbable material for fixation or scaffolding because of its controlled physical and chemical surface properties [15]. In the clinical application, PLLA scaffold were applied in the dental therapy for guided tissue regeneration/guided bone regeneration as a barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Poly-L-lactide (PLLA) has become the most popular bioresorbable material for fixation or scaffolding because of its controlled physical and chemical surface properties [15]. In the clinical application, PLLA scaffold were applied in the dental therapy for guided tissue regeneration/guided bone regeneration as a barrier.…”
Section: Introductionmentioning
confidence: 99%
“…However, for quantitative analyses, these methods make it difficult both to create controlled stress gradients in substrate samples and to accurately measure their local mechanical properties. To overcome these problems, injection-molded PLLA in combination with photoelastic measurements was proposed by Lee et al Their results suggested that this system can provide an effective system for mechanotaxis analysis [18].…”
Section: Discussionmentioning
confidence: 99%
“…While residual stress can be a mechanical stimulator for inducing bone remodeling [26], most in vitro studies of tensotaxis focused on the effects of tensile strain on cell behavior [3,23], with not much attention paid to the effects of compressive stress and strain [18]. In this study, a residual stress-controlled poly-L-lactide (PLLA) substrates, developed in our previous report [18], were used as substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its success greatly depends on the chemical and physical properties of the biomaterials. Recently, poly-l-lactide (PLLA) has become the most popular biodegradable material for scaffolding [1][2][3]. However, low proliferation rates and poor cell attachment were reported when cells were cultured on PLLA surfaces [4,5].…”
Section: Introductionmentioning
confidence: 99%